The Role Of Institutional Ownership In Human And Structural Capital Efficiency In Increasing Firm Value - Bryan Poaler; Kazia Laturette (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study investigates the impact of Intellectual Capital on company valuation in the technology industry in Indonesia, highlighting the role of institutional ownership as a moderator. Data covering 35 technology entities listed on the Indonesia Stock Exchange (IDX) during the period 2022 to 2024 are analyzed using multiple linear regression methods. The research findings show that Structural Capital Efficiency increases company valuation. However, Human Capital Efficiency cannot increase company valuation. Furthermore, institutional ownership is identified as positively moderating the correlation between Human Capital Efficiency and company valuation, indicating that the presence of institutional investors has the potential to increase market appreciation of the Human Capital aspect. This study underlines the significance of Intellectual Capital in the form of Human Capital Efficiency and Structural Capital Efficiency as well as institutional ownership in increasing the value of technology sector companies in Indonesia.